Strategi Pengembangan Desa Wisata Berkelanjutan dengan Pendekatan 4A (Attraction, Accessibility, Amenities, Ancillary) dalam Perspektif Maqashid Syariah (Studi Wisata Setigi Gresik) - Huril A'ini; Ayu, Intan (EKALAYA : Jurnal Ekonomi Akuntansi, 2024)
This research aims to analyze how sustainable tourism village development strategies are using the 4A approach from a maqashid sharia perspective. This type of research is qualitative research with descriptive data analysis methods where data collection techniques are carried out by means of observation, interviews and documentation. The instruments in this research are research tools which include a data collection form containing a list of questions for tourism managers and visitors, recording equipment, cameras and other tools that support the research data collection process. The results of the research show that the main components of 4A (Attraction, Amenity, Accessibility and Anciliary), namely the facilities are quite complete and good, but some facilities are still not utilized properly, and some facilities are outdated, damaged and neglected, requiring maintenance. By utilizing collaboration between other stakeholders, it can be a helpful and easier solution to build and maintain tourist facilities so that they can be sustainable. Then, the process of developing the Setigi Gresik tourist village often collides with the understanding of maqashid sharia, such as ensuring that the development of the tourist village does not only pay attention to material aspects, but also spiritual, social and humanitarian aspects.